Thyroid Stimulating Hormone (TSH) Is Associated With General and Abdominal Obesity: A Cohort Study in School-Aged Girls During Puberty in East China - Wang, Yingying; Dong, Xiaolian; Fu, Chaowei; Su, Meifang; Jiang, Feng; Xu, Dongli; Li, Rui; Qian, Junhua; Wang, Na; Chen, Yue; Jiang, Qingwu (Frontiers in Endocrinology, 2020)
Abstract Objectives: Although the association between thyroid stimulating hormone (TSH) and obesity in children has been investigated in several cross-sectional studies, no study evaluated this association among girls during puberty, which were in a key period closely related to the fluctuations of thyroid hormones and development of obesity. Therefore, we conducted a cohort study to investigate the association of general and abdominal obesity with TSH in girls during puberty. Setting and participants: A cohort study of 481 school-aged girls during puberty was conduct in four cities in the East Coast of China, with a baseline survey in 2017 and a follow-up survey in 2019. Outcome measures: Anthropometric indexes including height, weight and waist circumference (WC) were measured, and body mass index (BMI) was then calculated. Blood samples were collected to determine TSH and free thyroxine (FT4). Results: Of the 474 girls at baseline survey, the prevalences of BMI-based general obesity and WC-based abdominal obesity were 19.8% (94/474) and 21.7% (103/474), respectively. Compared with normal weight girls, the median serum TSH level was significantly higher in general obese girls (P=0.037), but not in abdominal obese girls (P=0.173). Multiple logistic regression models indicated that those with highest tertile of serum TSH level had a higher risk of BMI-based overweight/obesity (OR=1.83, 95% CI 1.01 to 3.32) as compared with those in the lowest tertile. Data from 435 girls prospectively followed-up for two years revealed that those with general or central obesity also had higher follow-up TSH level (P=0.004 and P=0.008, respectively). The TSH level for girls with general obesity at baseline but normal weight at follow-up was 0.45 mU/L (95%CI 0.11 to 0.79) higher than those with normal weight at baseline and follow-up. Conclusions: TSH was positively associated with both general and abdominal obesity among girls during puberty.